2002
DOI: 10.1093/pubmed/24.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and socio-economic inequalities in coronary heart disease, diabetes and risk factors in Europeans and South Asians

Abstract: The European pattern of inequalities is being established in South Asian men and women, possibly at a different pace in different subgroups. Future studies of inequalities should be large, separate Indian, Pakistani and Bangladeshi populations, study men and women separately and track changes over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
123
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 16 publications
11
123
1
Order By: Relevance
“…However, individuals within and between ethnic groups differ in their regional distribution of excess weight, hence BMI is confounded by variability in physique and remains a relatively crude index of risk. For example, Asians are now known to have both greater disease risk [24][25][26] and greater body fatness 27 than Europeans for any given BMI level, which has led to proposals for ethnic-specific BMI cutoffs to identify overweight and obesity. 13 In our own analyses, population differences in BMI did not match those in body shape.…”
Section: Discussionmentioning
confidence: 99%
“…However, individuals within and between ethnic groups differ in their regional distribution of excess weight, hence BMI is confounded by variability in physique and remains a relatively crude index of risk. For example, Asians are now known to have both greater disease risk [24][25][26] and greater body fatness 27 than Europeans for any given BMI level, which has led to proposals for ethnic-specific BMI cutoffs to identify overweight and obesity. 13 In our own analyses, population differences in BMI did not match those in body shape.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that medical treatment does not match the increased need of the immigrants and may possibly be explained by the lower socioeconomic (SES) status of immigrants. Results from recent studies have shown that individuals with a low SES have a poorer adherence regarding treatment with beta-blockers and statins after acute myocardial infarction (AMI) [7,8], and some studies have also indicated that ethnic differences in cardiovascular disease are caused by differences in SES [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In Western societies, low socio-economic status is a risk factor for type 2 diabetes and cardiovascular disease, but the extent to which socio-economic status can explain ethnic differences in the prevalence of these diseases between migrants and the host population is still under discussion [4,5]. In recent years, only a few studies from Europe have focused on the associations between diabetes prevalence, ethnicity, modifiable lifestyle factors and socio-economic status [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, only a few studies from Europe have focused on the associations between diabetes prevalence, ethnicity, modifiable lifestyle factors and socio-economic status [5,6].…”
Section: Introductionmentioning
confidence: 99%